Swiss Finance Banking, Finance, and Digitalization - Meier, Henri B. (Springer Nature, 2023)
How could a small country in the middle of Europe, surrounded by much bigger countries and economic giants like Germany and France and in direct competition with North American and Asian rivals, develop world-class, cutting-edge financial markets? Swiss Finance answers this question, separating myth from reality, by explaining how Switzerland managed dramatic pressures brought to bear on its financial markets during the past two decades, perhaps none of them so great as the: · Competitive challenges caused by changes in Switzerland's banking secrecy laws and practices, · Shifting tide of new wealth generation toward Asia (e.g., China, Singapore, and South Korea), · Burdensome federal stamp and withholding taxes, and · Digitalization of the financial services industry, including cybersecurity, cryptocurrencies, smart contracts, central bank digital currencies, the FinTech revolution, and DLT applications. Swiss Finance thoroughly analyzes Swiss financial markets' successes and challenges. It covers critical topics for practitioners and academics to fully understand this unique development in world financial markets and private wealth administration. ; Provides thorough coverage of Swiss financial markets, their development, status, and expected position in the global economy Discusses the dramatic changes that have taken place in global financial markets, which have affected Swiss financial governance, regulation, financial structures, and institutions Covers new topics such as financial digitalization, FinTech, the collaborative economy, the impact of cryptocurrencies, distributed ledger technologies, and smart contracts